Health threats resulting from soil and groundwater contamination in e-dumps on the Agbogbloshie example - Ewa Zieliński; Adriana Wielgus; Katarzyna Sas; Walery Zukow (Kazimierz Wielki University, 2018)
Rapid economic growth, an increasing urbanization and globalization caused increasing of consumption and production of e-waste. The biggest e-waste yards are located in developing countries, most of them nearby of big cities with a large population. Most of them are located nearby markets and water sources. Burning of e-waste at e-waste sites initially results in extreme localised contamination followed by migration of the heavy metals into waters and subsequent links of food chains by contaminated water, vegetables, fish, milk and meat consumption. E-waste workers suffer negative health effects through toxic smoke inhalation and skin contact, while the wider community are exposed to the heavy metals contaminants through smoke, dust, drinking water and food.